Capillary Microreactor for Initial Screening of Three Amine-Based Solvents for CO2 Absorption, Desorption, and Foaming - Ashok, Anchu; Ballout, Jaafar; Benamor, Abdelbaki; Al-Rawashdeh, Ma’moun (Frontiers in Chemical Engineering, 2022)
Microreactor is a very attractive laboratory device for screening conditions and solvents in an efficient, safe and fast manner. Most reported work on microreactors for CO2 capturing deals with absorption and mass transfer performance with a limited number of studies on solvent regeneration. For the first time, foaming, which is a major operational challenge of CO2 capturing is being studied in combination with absorption and desorption in a capillary microreactor setup. To demonstrate the setup capabilities, three known amine-based solvents (MEA, MDEA, and AMP) were selected for the screening and evaluation studies. MEA had the highest CO2 absorption efficiency while MDEA had the lowest one. CO2 absorption efficiency increased with temperature, liquid flow rate, and amine concentration as per the literature. During the absorption work, the Taylor flow regime was maintained at the reactor inlet. CO2 desorption of loaded amine solutions was investigated at different concentrations and temperatures up to 85 oC. MDEA solution had the highest desorption efficiency, followed by AMP and the least desorption efficiency was that of MEA. Foaming experimental results showed that MEA had a larger foaming region compared to AMP. However, more foaming happened with AMP at higher gas and liquid flow rates. A plug flow mathematical reactor model was developed to simulate the MEA-CO2 system. The model captured well the performance and trends of the studied system, however the absolute prediction deviated due to uncertainties in the used physical properties and mass transfer correlation. Selecting a solvent for chemical absorption depends on many more factors than these three studied parameters. Still, microreactor proves a valuable tool to generate experimental results under different conditions, with the least amount of consumables (less than 1 L solvents were used), in a fast manner, combined with a knowledge insight because of the uniqueness of the Taylor flow regime.